Treatment of organic resources before soil incorporation in semi-arid regions improves resilience to El Niño, and increases crop production and economic returns - Smith, Jo; Nayak, Dali; Albanito, Fabrizio; Balana, Bedru; Black, Helaina; Boke, Shiferaw (IOP Publishing, 2019)
The use of limited organic resources to build resilience to drought in semi-arid regions was investigated using systems modelling. The study focused on Halaba in Ethiopia, drawing on biophysical and socio-economic data obtained from a survey of farms before, during and after the 2015/16 El Niño event. Using a simplified weather dataset to remove noise from weather fluctuations, a ten yearly El Niño was demonstrated to cause significant long-term degradation of soil, reducing crop yields by 9%–14% and soil carbon by 0.5%–4.1%; more frequent droughts would increase this impact. Farmers in Halaba usually apply manures to soils untreated. Counteracting the impact of El Niño on soil degradation is possible by increasing application of untreated manure, but would result in a small net cost due to loss of dung as fuel. By composting manure its recalcitrance increases, allowing soil degradation to be counteracted without cost. The best option investigated, in terms of both food and fuel security, for households with access to water and finances needed for anaerobic digestion (500–2000 US$), is to use manure to produce biogas and then apply the nutrient-rich bioslurry residue to the soil. This will result in a significant benefit of over 5000 US$ per decade from increased crop production and saved fuel costs. However, many households are limited in water and finances; in that situation, the much cheaper pyrolysis cook-stove (50 US$) can provide similar economic benefits without the need for water. The biochar residue from pyrolysis is highly recalcitrant, but pyrolysis results in loss of nutrients, so may result in lower yields than other uses of manures. This may be countered by using biochar to capture nutrients from elsewhere in the farm, such as from animal housing or compost pits; more work is needed to quantify the impact of treated biochar on crop yields.